THE EFFECT OF COOPERATIVE INTEGRATED READING AND COMPOSITION (CIRC) TECHNIQUE ON READING COMPREHENSION OF THE SECOND YEAR STUDENTS OF SMPN 1 KUBU ROKAN HILIR IN DESCRIPTIVE TEXTS - Nurisa, Nurisa; Prawati, Atni; M. Syarfi, M. Syarfi (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2018)
Abstract: This research was designed to experiment the effect of cooperative integrated reading and composition (CIRC) technique on the students’ reading comprehension of descriptive texts. The aim was to find out whether there is any significant effect of using CIRC technique on the students’ reading comprehension of descriptive texts. This research took place in SMPN 1 Kubu, Rokan Hilir that collected from January to October 2017. The try out class was VIII4 (25 students) and the sample was VIII2 (25 students) chosen by purposive sampling. This is a pre-experimental research with one group pre-test post-test design. This research used quantitative data and the instrument used to collect the data is a reading test in multiple choice forms. The tests consisted of 40 items. As the result, the mean score of pre-test is 46.52 and the mean score of post-test is 59.80. In other words, the mean score of post-test is higher than the mean score of pre-test. The result also showed that the value of t-test (5.226) is higher than t-table (2.064) at the significance level 5%. It means that Alternative Hypothesis (Ha) is accepted and Null Hypothesis (Ho) is rejected. Hence, there is a significant effect of using CIRC technique on reading comprehension of the second year students of SMPN 1 Kubu, Rokan Hilir in Descriptive texts.Key Words: Student’s Reading Comprehension, CIRC Technique, Descriptive Texts.